2015
DOI: 10.1016/j.cub.2015.08.022
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Control of Synaptic Remodeling through Regulated Expression of an Immunoglobulin Superfamily Protein

Abstract: SUMMARY Neural circuits are actively remodeled during brain development but the molecular mechanisms that trigger circuit refinement are poorly understood. Here we describe a transcriptional program in C. elegans that regulates expression of an Ig domain protein, OIG-1, to control the timing of synaptic remodeling. DD GABAergic neurons reverse polarity during larval development by exchanging the locations of pre- and postsynaptic components. In newly born larvae, DDs receive cholinergic inputs in the dorsal ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
89
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(98 citation statements)
references
References 21 publications
(30 reference statements)
9
89
0
Order By: Relevance
“…Indeed, an example of synapse refinement in the absence of axon growth was described in the mammalian central nervous system, where imaging of individual axonal arbors of retinal ganglion cells showed that retinogeniculate synapse remodeling can occur without axon retraction. 33 Four decades after John White's seminal work, we have learned a great deal about DD remodeling, which has provided a rich platform to study the temporal cues 4,6,7,9,10,14,17 as well as the cellular mechanisms that underlie this complete inversion of synaptic connectivity. [22][23][24] Our findings have also revealed a novel role of dynamic MTs in regulating synaptic vesicle transport in the absence of neurite growth or pruning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, an example of synapse refinement in the absence of axon growth was described in the mammalian central nervous system, where imaging of individual axonal arbors of retinal ganglion cells showed that retinogeniculate synapse remodeling can occur without axon retraction. 33 Four decades after John White's seminal work, we have learned a great deal about DD remodeling, which has provided a rich platform to study the temporal cues 4,6,7,9,10,14,17 as well as the cellular mechanisms that underlie this complete inversion of synaptic connectivity. [22][23][24] Our findings have also revealed a novel role of dynamic MTs in regulating synaptic vesicle transport in the absence of neurite growth or pruning.…”
Section: Discussionmentioning
confidence: 99%
“…17 In L1 animals, the post-synaptic GABA-A receptor UNC-49 is expressed exclusively in the ventral muscles. 18 Following the birth of the VD neurons in L2 animals, UNC-49 receptor clusters appear in both ventral and dorsal muscles.…”
Section: Factors That Regulate the Timing Of Dd Remodelingmentioning
confidence: 99%
“…A second, Ig-domain containing, gene, oig-1 , was recently found to be a transcriptional target of LIN-14. OIG-1 functions as a synaptic organizer to maintain DD’s early synaptic pattern (He et al, 2015; Howell et al, 2015). Loss of oig-1 results in premature rewiring of DD neurons, partially resembling lin-14 null.…”
Section: Introductionmentioning
confidence: 99%
“…The nicotinic AChR subunit ACR-12 is a constituent of GABA neuron iAChRs. ACR-12::GFP clusters localize opposite ACh release sites and relocate appropriately during developmental remodeling, suggesting that these clusters report mature postsynaptic structures (Petrash et al, 2013;He et al, 2015). We examined the distribution of ACR-12:: GFP in the dorsal nerve cord where the majority of chemical synaptic inputs to VD neurons occur (VD synaptic contacts with muscles are exclusively ventral) (White et al, 1986).…”
Section: Unc-3 Transcriptional Regulation Coordinates Cholinergic Synmentioning
confidence: 99%